2018
DOI: 10.1103/physreve.98.022118
|View full text |Cite
|
Sign up to set email alerts
|

Quantum thermal transistor based on qubit-qutrit coupling

Abstract: A quantum thermal transistor is designed by the strong coupling between one qubit and one qutrit which are in contact with three heat baths with different temperatures. The thermal behavior is analyzed based on the master equation by both the numerical and the approximately analytic methods. It is shown that the thermal transistor, as a three-terminal device, allows a weak modulation heat current (at the modulation terminal) to switch on and off and effectively modulate the heat current between the other two t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 76 publications
(74 reference statements)
0
51
0
Order By: Relevance
“…In this section, we turn our attention to the systems featured by distinct asymmetries, such as the qubits with different frequencies or asymmetric couplings to their reservoirs. Indeed, inspired by the manipulation and control of the thermal transport in micro-scale, such asymmetric systems were widely investigated in the thermal diode and thermal transistor [37][38][39][40][41][42][43][44][45]. In the following, we will study the heat transport and, at the same time, study whether the inter-system interaction can be ignored or not when modeling the system-environment interaction.…”
Section: Asymmetric Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we turn our attention to the systems featured by distinct asymmetries, such as the qubits with different frequencies or asymmetric couplings to their reservoirs. Indeed, inspired by the manipulation and control of the thermal transport in micro-scale, such asymmetric systems were widely investigated in the thermal diode and thermal transistor [37][38][39][40][41][42][43][44][45]. In the following, we will study the heat transport and, at the same time, study whether the inter-system interaction can be ignored or not when modeling the system-environment interaction.…”
Section: Asymmetric Systemmentioning
confidence: 99%
“…By means of an effective harmonic Hamiltonian, a quantum thermal transport through anharmonic systems was studied within the framework of the nonequilibrium Green's function method [35]. Besides, quantum devices such as heat rectifier, thermal memory, and thermal ratchet, have also become goals of controlling thermal transport in quantum thermodynamics [36][37][38][39][40][41][42][43][44][45]. It was found that, by using the quantum master equation, thermal rectification in anisotropic Heisenberg spin chains could change sign when the external homogeneous magnetic field was varied [43].…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of these controllable quantum platforms (systems), some studies focus on the redefinitions of some concepts, such as work and heat [ 31 , 32 , 33 , 34 ], and the verification and modification of thermodynamics second law [ 35 ] in quantum domain. Others concentrate on heat control/management [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] in order to design the quantum thermodynamic process (or quantum thermal machines) that can implement a certain task (or multi-task) using thermal resources [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have been devoted to thermal rectification [ 60 , 61 , 62 ]. Currently, the quantum thermal transistor [ 39 ] to implement heat amplification, and various quantum control devices of heat current with a specific function have been proposed, such as quantum thermal diodes [ 47 , 63 ], quantum heat switch [ 64 ], transistors [ 48 , 49 ], thermometers [ 50 , 51 , 52 , 53 ], thermal valves [ 54 ] and many-body quantum thermal rectification [ 65 ]. Most currently, to design a multifunctional quantum thermal device [ 20 , 55 , 56 , 57 , 58 , 59 , 66 ], i.e., integrating the multiple functions into a single device, has become an interesting and active subject.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in the field of heatronics, i.e., the management of heat flow at the nanoscale, give opportunities to * cyril.elouard@gmail.com pass this bottleneck. Last advances include the design and experimental realization of nanoscale thermal rectifiers [7][8][9][10][11][12], thermal transistors [13][14][15][16][17][18][19], and nanoelectronic heat engines [20][21][22][23][24][25][26]. Even more recently, nanoscale heat manipulation was associated with the properties of quantum circuits and fine temperature measurements [27,28].…”
mentioning
confidence: 99%